HUBUNGAN KEKERABATAN ANTAR POPULASI JATI (Tectona Grandis,Linn.F.) BERDASARKAN PENANDA RAPD (RANDOM AMPLIFIED POLYMORPHIC DNA) - AYPBC Widyatmoko; Anto Rimbawanto; Abdul Razaq Chasani (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2013)
Information on genetic relationship amongst teak (Tectona grandis Linn.f) populations in Indonesia is important, in order to maintain the high genetic diversity of the species and to ensure the origin of commercial planting materials. In this study, 94 loci from 25 RAPD primers were used for analyzing genetic diversity and genetic relationship among 30 populations of teak which collected from provenance trial in Bojonegoro and its populations in Sulawesi. Mean genetic diversity (h) of the 30 populations was 0.184, and mean genetic distance between populations (D) was 0.441. Based on cluster analysis, 30 populations of teak were divided into 3 groups. The first group consisted of Burma, the second group consisted of Jawa, India, Indochina and Thailand populations, and the third group consisted of all populations in Sulawesi. High genetic distance between Jawa’s and Sulawesi’s populations can be used to differentiate seed/seedling from both regions.